Decision-Making in Adult Cranial Vault Reconstruction. Issue 1 (July 2021) - Brichacek, Michal; Antonyshyn, Oleh; Edwards, Glenn; Mainprize, James G.; da Costa, Leo
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Define and classify different types of cranial defects 2. Compare both autologous and alloplastic options for reconstruction 3. Develop an optimal approach for cranial vault reconstruction in various clinical scenarios. Summary: Defects of the cranium result from various causes, including traumatic loss, neurosurgical intervention, skull tumors, and infection. Cranial vault reconstruction aims to restore both the structural integrity and surface morphology of the skull. To ensure a successful outcome, the choice of appropriate cranioplasty reconstruction will vary primarily based on the cause, location, and size of the defect. Other relevant factors that must be considered include adequacy of soft-tissue coverage, presence of infection, and previous or planned radiation therapy. This article presents an algorithm for the reconstruction of various cranial defects using both autologous and alloplastic techniques, with a comparison of their advantages and disadvantages.